2020
DOI: 10.51441/biomedica/5-136
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Validity and Reliability of Scores of Multiple Choice and Short Essay Questions

Abstract: Background and Objective: Assessment of learning plays a vital role in curriculum allowing faculty to evaluate the achievement of student and educational process. Quality assurance of the assessments is done to assess the quality of teaching and learning. A study is therefore conducted to find the discriminant validity and reliability of scores of Multiple Choices and Short Answer Questions.Methods: A correlation study was conducted on 272 second year MBBS students of Fatima Memorial College of Medicine and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
2
2
0
Order By: Relevance
“…It is more discriminating than multiple questions. Our study's results are in agreement with those in the studies by Jaleel et al (2020) [17], Kunjappagounder et al [16], and Maryani et al [18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is more discriminating than multiple questions. Our study's results are in agreement with those in the studies by Jaleel et al (2020) [17], Kunjappagounder et al [16], and Maryani et al [18].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the present study revealed positive linear correlations between SEQs, MCQs, and total grades. These correlations were also reported in other subjects, such as pharmacology [25], otorhinolaryngology [26], pediatrics [27], and basic medical sciences, including physiology and medical biochemistry [4,17].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…High-quality MCQs are considered an appropriate assessment tool because they can cover a wide range of knowledge and domains of knowledge [ 1 ]. Many authors reported the validity and reliability of MCQs [ 2 6 ]. The validity and reliability of MCQs can be ensured pre-construction by the presence of the content material from which the MCQs will be constructed and a blueprint [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%